Electronic Document Management Systems for the Transportation Construction Industry. Issue 1 (2nd January 2021) - Guo, Fangyu; Jahren, Charles T.; Turkan, Yelda
ABSTRACT: The implementation of various technologies typically produces a considerable amount of digital data for transportation agencies; therefore, it is desirable to have electronic document management (EDM) systems to promote efficient data-sharing among stakeholders. Although EDM systems have been implemented in the building construction industry and their benefits are well understood, they are not as common in the transportation design and construction industry. There are only a few agencies that have broadly implemented EDM with limited research having been conducted on this topic. Accordingly, the purpose of this paper is to present and analyze the current state of the EDM system implementation within leading US transportation agencies and to develop a framework for the selection and implementation of EDM systems for other agencies. This article describes four case studies that were conducted with four transportation agencies in the US who are at the frontiers in the implementation of EDM systems. Current EDM practices at these agencies as well as the associated benefits and challenges were documented. By comparing and contrasting these case studies, the common functionalities and unique characteristics of various EDM systems were summarized and a framework was developed to guide transportation agencies with the selection and implementation of EDM systems.